Peran Stakeholder Untuk Mengembangkan Desa Wisata Melalui Industri Kerajinan di Desa Loyok, Kecamatan Sikur - Nildafilyandini Nildafilyandini; Ni Nyoman Ngurah Tanya Wedhrani; Lalu Gigih Izzul Islam; Nita Dianti; Ika Wijayanti (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
Tourism Villages are increasingly becoming the main focus in developing local tourism in Indonesia. One prominent example is Loyok Village, which is located in Sikur District. This village is known for its unique handicraft industry, such as bamboo weaving. This research examines the important role of stakeholders in supporting and developing the potential of tourist villages through the development of local craft industries. The type of research used in this research is qualitative research and the research approach is case study. The data collection techniques used by researchers are interviews, observation and documentation. In-depth interviews were conducted with various stakeholders, such as local entrepreneurs, village government and local communities involved in the management and development of tourist villages. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results found that collaboration between various stakeholders is key in improving, marketing, skills training and promoting tourism in Loyok village. Thus, this research provides valuable insights for the development of other tourist villages in Indonesia, especially in the context of managing the craft industry to improve the welfare of local communities and expand tourism attractions. The cooperation and communication that exists between stakeholders is relatively good, thereby speeding up the implementation process of developing the Bamboo Woven Craft Industry.